Anthro-apology? negotiating space for interdisciplinary collaboration and in-depth anthropology in the CGIAR - Verma, R.; Russell, D.; German, L. (Springer, 2010)
Equitable interdisciplinary teamwork is easier said than done. For, it is not simply a matter of adding a “pinch” of social science into a larger interdisciplinary team, and stirring. Putting interdisciplinarity into action requires a more distilled and nuanced approach involving negotiation, bargaining and, sometimes, contestation and resistance between and among different domains of disciplinary actors, knowledge, meanings and understanding. The overarching goal for anthropologists and sociocultural scientists is to integrate theories, methodologies, and practices of the study of culture, politics, and social relations into agricultural and natural resource management research, as well as to integrate themselves into larger interdisciplinary teams on an equal footing. As McDonald argues in his call for a discussion on keeping the culture in agriculture, “by putting culture squarely at the center of any analysis of agriculture, we seek to “put people first” by exploring the complex ways that people conceptualize, give meaning to, and organize around agriculture” (McDonald 2005, p. 71). However, putting culture into the analysis of agriculture in research systems long dominated by biophysical scientists and approaches, such as within research centers of the Consultative Group for International Agricultural Research (CGIAR), is challenging. This chapter describes the various dilemmas, challenges, and opportunities encountered by sociocultural scientists in interdisciplinary projects within the CGIAR. It argues that to more effectively address the needs and realities of vulnerable women and men at the grassroots, agricultural research systems must take more steps to fully integrate social, cultural, and political lines of inquiry into their core mandates.